2018
DOI: 10.1021/acs.molpharmaceut.8b00270
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Glioblastoma Targeting Ability of Carfilzomib Enabled by a DA7R-Modified Lipid Nanodisk

Abstract: The robust proliferation of tumors relies on a rich neovasculature for nutrient supplies. Therefore, a basic strategy of tumor targeting therapy should include not only killing regular cancer cells but also blocking tumor neovasculature. D-peptide A7R, which was previously reported to specifically bind vascular endothelial growth factor receptor 2 (VEGFR2) and neuropilin-1 (NRP-1), could achieve the goal of multitarget recognition. Accordingly, the main purposes of this work were to establish a carfilzomib-loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…To address these limitations, different bioconjugates between poly­(ethylene glycol) (PEG) and target ligands including human H-ferritin, chlorotoxin, cyclic arginine-glycine-aspartic acid (c-RGD), and d -peptide have been developed to cross BBB and serve as active targeting theranostics. For example, Lu et al . reported RGD-targeted hollow gold nanospheres for photoacoustic imaging and PTT of GMB .…”
mentioning
confidence: 99%
“…To address these limitations, different bioconjugates between poly­(ethylene glycol) (PEG) and target ligands including human H-ferritin, chlorotoxin, cyclic arginine-glycine-aspartic acid (c-RGD), and d -peptide have been developed to cross BBB and serve as active targeting theranostics. For example, Lu et al . reported RGD-targeted hollow gold nanospheres for photoacoustic imaging and PTT of GMB .…”
mentioning
confidence: 99%
“…PEGylated LND morphologies were first described in the late 1990s 41 , and a few groups have explored this type of LND for drug delivery 42 44 , but the tumour-penetrating capacity of these nanomaterials has not been analysed in detail in vivo. Our computational models of LND versus liposome pore penetration demonstrate that the lack of an enclosed aqueous volume makes nanodiscs amenable to dramatic deformations in response to weak forces, favouring effective convection or diffusion through ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Meng et al (1999) described that DHE antitumor activity, as also observed for structurally related compounds, is explained through inhibition of the proteasome function, but epoxyketonecontaining antitumor natural products may differ in their antiproliferative activity, proteasome subunit binding specificity, and rates of proteasome inhibition. Considering the intriguing structure-activity relationship for this class of compounds (Kim et al, 1999;Groll et al, 2000) and the emerging knowledge on the antiglioma effects of the proteasome inhibitors (Di et al, 2016;Zhang et al, 2018;Veggiani et al, 2019), we further assayed DHE and BRA-346 epoxyketone-containing fraction in glioma cells HOG and T98G, revealing their potent antiproliferative effects in the ng/mL-range and the modulation of ER-stress related and pro-apoptotic related genes, along with unfolded protein response and the ubiquitin-proteasome system itself.…”
Section: Discussionmentioning
confidence: 99%